Epidermal growth factor receptor gene copy number may predict lapatinib sensitivity in HER2-positive metastatic breast cancer. (April 2013) - Fabi, Alessandra; Merola, Roberta; Ferretti, Gianluigi; Di Benedetto, Anna; Antoniani, Barbara; Ercolani, Cristiana; Nisticò, Cecilia; Papaldo, Paola; Ciccarese, Mariangela; Sperduti, Isabella; Vici, Patrizia; Marino, Mirella; et al.
<x xml:space="preserve">Abstract</x> Objective: Lapatinib, a dual HER2/EGFR tyrosine kinase inhibitor (TKI), associated to capecitabine represents the treatment of choice in HER2-positive metastatic breast cancer (BC) patients in progression after trastuzumab-based therapy. Though lapatinib-based therapy prolongs the time to progression, its efficacy is often limited by the development of drug resistance. It is aimed to evaluate novel biomarkers predictive of lapatinib response, we analyzed EGFR protein and gene status in a series of 50 metastatic HER2-positive BC patients. Methods: Lapatinib was given at 1250 mg/day continuously and capecitabine at 2000 mg/m2/day every 3 weeks. EGFR protein expression and gene copy number (GCN) were assessed by immunohistochemistry and FISH, respectively. Receiver operating curve (ROC) analysis identified the value of > 3.36 EGFR copies/nucleus as the cut-off point able to discriminate responders versus non-responders. Results: A statistical significant correlation between EGFR GCN value > 3.36 and response to lapatinib (p = 0.01) was found. Cox regression analysis further supported these findings evidencing that HER2 score 3+ and EGFR GCN increase are positive predictor factors of lapatinib response. Conclusions: Though further investigations are needed to confirm these findings, EGFR GCN could be a suitable screening to identify the subset of BC patients particularly responsive to the dual TKI lapatinib.